2003
DOI: 10.1063/1.1555292
|View full text |Cite
|
Sign up to set email alerts
|

Crossovers from in-plane to perpendicular anisotropy in magnetic tunnel junctions as a function of the barrier degree of oxidation

Abstract: Pt/Co/M sandwiches (M=Al, Ta, Cr) were prepared by sputtering. The M capping layer was oxidized either by natural oxidation in air or by exposure to an oxygen plasma. By measuring the extraordinary Hall effect in these systems, we observed that the magnetic anisotropy of the Co electrode is extremely sensitive to the degree of oxidation of the capping layer. In particular, when M=Al, the magnetic anisotropy is found in plane when the AlOx layer is under or overoxidized whereas it is out of plane when this oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 7 publications
3
65
1
Order By: Relevance
“…A magnetic coupling at the electrode interface also exists in other common material combinations like AlOx-Co [37,38]. This needs to be considered when using the electrode rotation technique to determine the spin-lifetime anisotropy.…”
Section: A Rotating the Electrode Magnetizationmentioning
confidence: 99%
“…A magnetic coupling at the electrode interface also exists in other common material combinations like AlOx-Co [37,38]. This needs to be considered when using the electrode rotation technique to determine the spin-lifetime anisotropy.…”
Section: A Rotating the Electrode Magnetizationmentioning
confidence: 99%
“…Fully perpendicular magnetic tunnel junctions (pMTJ) constitute the storage element of spin-transfer torque magnetoresistive random access memory (STT-MRAM) [1][2][3][4][5][6]. STTMRAMs are very promising emerging nonvolatile memories since they combine nonvolatility, low energy consumption, high thermal stability, and almost unlimited endurance.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning here that perpendicular magnetic anisotropy has been reported, both theoretically and experimentally, in the Fe/MgO system [39], but it has also been shown that it strongly depends on the oxidation degree of interfaces [40,41]. In addition, AF coupling due to interlayer exchange coupling has also been reported for the Fe/MgO/Fe system for MgO barrier thicknesses around 1 nm [42].…”
Section: Resultsmentioning
confidence: 89%